High Glucose Exacerbates TNF-α-Induced Proliferative Inhibition in Human Periodontal Ligament Stem Cells through Upregulation and Activation of TNF Receptor 1 - Wenjun Zhu; Qihong Qiu; Haoyuan Luo; Fuping Zhang; Juan Wu; Xiaorui Zhu; Min Liang (Stem Cells International)
Objective. This research is aimed at investigating how high glucose affects the proliferation and apoptosis in periodontal ligament stem cells (PDLSCs) in the presence of TNF-α. Methods. PDLSCs obtained from periodontal healthy permanent teeth were treated under either high-glucose condition (30 mmol/L, G30 group) or normal glucose condition (5.6 mmol/L, G5.6 group) in the presence or absence of TNF-α (10 ng/ml) for 2 to 6 days. Cell proliferation and cell cycle were evaluated by CCK-8, EdU incorporation assay, and flow cytometry. Cell apoptosis was assessed by annexin V/PI staining. Protein expression was detected by western blotting. Cellular ROS expression was evaluated by CellROX labeling and flow cytometry. Specific antibodies targeting TNFR1 and TNFR2 were used to block TNF-α signaling. Vitamin C was also used to verify if the blockage of ROS can rescue PDLSCs in the presence of high glucose and TNF-α. Results. CCK-8 assay showed that high glucose exacerbated TNF-α-induced cell viability inhibition (57.0%, 85.2%, and 100% for the G30+TNF-α group, G5.6+TNF-α group, and control group, respectively) on day 6. High glucose increased protein expression of TNFR1 compared with the control group on day 2 (1.24-fold) and day 6 (1.26-fold). Blocking TNFR1 totally reversed the proliferative inhibition in G30+TNF-α group. The addition of vitamin C or TNFR1 antibody totally reversed the elevation of intracellular ROS expression caused by high glucose and TNF-α. Vitamin C partially restored cell proliferation in the presence of high glucose and TNF-α. Conclusion. High glucose exacerbates TNF-α-induced proliferative inhibition in human periodontal ligament stem cells through the upregulation and activation of TNF receptor 1. Inhibition of intracellular ROS expression by vitamin C partially rescues PDLSCs in terms of cell proliferation.